ANALISIS KINERJA EKSPOR KOMODITAS KARET INDONESIA KE AMERIKA LATIN - Muharami, Ghufrani; Novianti, Tanti (Jurnal Agribisnis Indonesia, 2018)
ABSTRACTIndonesia’s export dependency on traditional marketcan be minimized by diversifying export markets. Rubber (HS 4001-natural rubber) is one of Indonesia's main export commoditiesto Latin America. Given Indonesia's export growth to Latin America, the region could become potential market for diversifying export markets. This study aimed to analyze the competitiveness of rubber commodities and the factors affecting Indonesian rubber exports to Latin America, using secondary data ie cross section data of 6 export destination countries (Argentina, Brazil, Chile, Colombia, Mexico, and Peru) and time series data during 7 years (2009-2015). The analysis tools used RCA, EPD, and gravity model. Based on average RCA value, HS 4001 (natural rubber) Indonesia’s product is able to compete in Latin American market. Meanwhile EPD analysis identified, Indonesia’s main commodities are on rising star, falling star, and retreat positions. Gravity model analysis shows that the factors which influence Indonesia’s export to America Latin are GDP of export destination countries, real exchange rate, export price, and economic distance.